After ethnic conflict policy-making in post-conflict Bosnia and Herzegovina and Macedonia - Koneska, Cvete (Southeast european studies, 2014)
Focussing on the interactions between political elites and attempts to reach agreement across ethnic lines in Bosnia and Macedonia the book examines the impact that institutional factors can have on political actors and the decisions they make.